2001
DOI: 10.1152/ajpheart.2001.281.3.h1334
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+/Ca2+ exchange by KB-R7943: transport mode selectivity and antiarrhythmic consequences

Abstract: The Na+/Ca2+ exchanger plays a prominent role in regulating intracellular Ca2+ levels in cardiac myocytes and can serve as both a Ca2+ influx and efflux pathway. A novel inhibitor, KB-R7943, has been reported to selectively inhibit the reverse mode (i.e., Ca2+ entry) of Na+/Ca2+ exchange transport, although many aspects of its inhibitory properties remain controversial. We evaluated the inhibitory effects of KB-R7943 on Na+/Ca2+ exchange currents using the giant excised patch-clamp technique. Membrane patches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 53 publications
9
78
0
Order By: Relevance
“…4 ] i dependency of e T ). This is consistent with previous results showing that KBR preferentially blocks the Ca 2ϩ influx (reverse) mode of the cardiac NCX rather than the extrusion (forward) mode (2,10,25,39,45) and that KBR inhibits Ca 2ϩ influx through NCX under Na ϩ -loaded conditions in rat myocardium (18,38,41,49). Furthermore, it has been shown that Ca 2ϩ influx (via reversal of NCX) is essential for digitalisinduced potentiation of cardiac basal energy expenditure (15).…”
Section: Effect Of Ncx Inhibition By Kbrsupporting
confidence: 92%
“…4 ] i dependency of e T ). This is consistent with previous results showing that KBR preferentially blocks the Ca 2ϩ influx (reverse) mode of the cardiac NCX rather than the extrusion (forward) mode (2,10,25,39,45) and that KBR inhibits Ca 2ϩ influx through NCX under Na ϩ -loaded conditions in rat myocardium (18,38,41,49). Furthermore, it has been shown that Ca 2ϩ influx (via reversal of NCX) is essential for digitalisinduced potentiation of cardiac basal energy expenditure (15).…”
Section: Effect Of Ncx Inhibition By Kbrsupporting
confidence: 92%
“…Using a variety of techniques, KB-R7943 was also found to exhibit transport mode selectivity, whereby inhibition of the reverse transport mode was favored (Iwamoto et al, 1996;Watano et al, 1996;Elias et al, 2001; but see Kimura et al, 1999). The site of action of KB-R7943 remains unknown, although amino acid residues (particularly Gly833) within the ␣-2 repeat region of the exchanger have been reported to markedly affect drug sensitivity (Iwamoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…influx) by NCX much more effectively than the forward mode (Iwamoto et al, 1996(Iwamoto et al, , 2004Elias et al, 2001). In addition, KB-R7943 is 3-fold more effective on NCX3 than on NCX1 and NCX2 , whereas SEA0400 predominantly blocks NCX1 compared with NCX2 and NCX3 (Iwamoto et al, 2004).…”
Section: Camentioning
confidence: 92%